Detection of the spatiotemporal field of a single-shot terahertz pulse based on spectral holography - 王晓雷 费扬 李璐杰 王强 朱竹青 (Chinese physics B, 2014)
According to electro-optical sampling theory, we propose a new method to detect the spatiotemporal field of a single- shot terahertz pulse by spectral holography for the first time. The single-shot terahertz pulse is coupled into a broadened chirped femtosecond pulse according to electro-optical sampling theory in the detecting system. Then the reference wave and the signal wave are split by Dammann grating and spread into the interference band-pass filter. The filtered sub-waves are at different central-frequencies because of the different incident angles. These sub-waves at different central-frequencies interfere to form sub-holograms, which are recorded in a single frame of a charge coupled device （CCD）. The sub-holograms are numerically processed, and the spatiotemporal field distribution of the original terahertz pulse is reconstructed. The computer simulations verify the feasibility of the proposed method.